PERUBAHAN DESAIN BUSANA ADAT PENGANTIN WANITA DI KOTA PARIAMAN SUMATERA BARAT - Cindi Harmelia; Yuliarma Yuliarma (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2021)
This research aims to describe changes in the design of brides' clothes in Pariaman City including silhouettes, shapes, materials, colors, motifs and ornamental techniques. In addition there are complements, accessories, ways of use and, aesthetic meaning contained in it. This research method is qualitative descriptive research with primary and secondary data types. Data is collected using observation, interview and documentation techniques. Data analysis uses interactive analysis collection techniques related to the subject matter being studied. The results showed that 1) Women's traditional top clothes are called kuruang basiba clothes and lower clothes with racing fabrics undergo design changes in terms of silhouettes that were once I is now silhouette A. The shape is in the form of airy and loose clothes, but now changed with clothes that show